“Jordan First”: Tribalism, Nationalism and Legitimacy of Power in Jordan - Al Oudat, Mohammed Ali; Alshboul, Ayman (Intellectual Discourse, 2010)
Abstract: The significance of tribal identity in Jordan can be seen in the special relationship of traditional institutions with the state, which shows both the fluctuation in the concept of tribalism and how tribalism can be better understood by viewing it through the perspective of “Jordanian nationalism”. This relationship has created confusion on the local and national levels about how the state system should work through its institutions. Furthermore, the process of democratization is only a façade; Jordan is supposedly a constitutional monarchy, but in fact the king holds absolute power. The parliament’s autonomy has been minimal, in other words, the parliament is a symbol of democracy but is widely perceived as non-representative. This paper examines the regime security strategy “Jordan First” and the particularity of Jordanian identity through its relationship to the concept of a Jordanian national consensus.